PENGEMBANGAN BAHAN AJAR VIDEO ANIMASI BERBANTUAN POWTOON PADA MATERI MENGAPA KITA PERLU MAKAN DAN MINUM DI SEKOLAH DASAR - Novi Indriyani; R. Teti Rostikawati; Yudhie Suchyadi (STKIP Subang, 2025)
Novi Indriyani, 037121013. Development of Animation Video Teaching Materials Assisted by Powtoon on the Material Why We Need to Eat and Drink in Elementary Schools. This study aims to develop, determine the feasibility, and evaluate the effectiveness of the designed teaching materials. The method used is the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The trial was conducted in class V SDN Bubulak 02 Bogor City with 23 students. In this study, validation tests were carried out on animated video teaching material products by media experts, language experts, and material experts. The validation results by media experts obtained 100% with very feasible criteria, language experts obtained 100% with very feasible criteria, material experts by lecturers obtained 94% with very feasible criteria, and material experts by teachers obtained 96% with very feasible criteria. The results of the student response questionnaire were 91% and the teacher response questionnaire was 96% with a very good category. Strengthened by the results of the N-Gain effectiveness test with an average learning outcome score of 0.78 in the high category. Thus, it can be concluded that Powtoon-assisted animated video teaching materials are very effective and practical to use in the learning process, and are able to improve student understanding.